Study Protocol: Transitions in Adolescent Girls (TAG) - Barendse, Marjolein E.A.; Vijayakumar, Nandita; Byrne, Michelle L.; Flannery, Jessica E.; Cheng, Theresa W.; Flournoy, John C.; Nelson, Benjamin W.; Cosme, Danielle; Mobasser, Arian; Chavez, Samantha J.; Hval, Lauren; Brady, Bernadette; et al. (Frontiers in Psychiatry, 2020)
Background: Despite recent studies linking pubertal processes to brain development, as well as research demonstrating the importance of both pubertal and neurodevelopmental processes for adolescent mental health, there is limited knowledge of the full pathways and mechanisms behind the emergence of mental illnesses such as depression and anxiety disorders in adolescence. The Transitions in Adolescent Girls (TAG)1 study aims to understand the complex relationships between pubertal development, brain structure and connectivity, the behavioral and neural correlates of social and self-perception processes, and adolescent mental health in female adolescents. Methods: The TAG study includes 174 female adolescents aged 10.0 to 13.0 years, recruited from the local community in Lane County, Oregon, USA. The participants, along with a parent/guardian, will complete three waves of assessment over the course of three years; the third wave is currently underway. Each wave includes collection of four saliva samples (one per week) and one hair sample for the assessment of hormone levels and immune factors; an MRI session including structural, diffusion, resting-state functional and task-based functional scans; the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS), a diagnostic interview on current and lifetime mental health; production of a short self-narrative video; and measurement of height, weight, and waist circumference. The functional MRI tasks include a self-evaluation paradigm and a self-disclosure paradigm. In addition, adolescents and their parents/guardians complete a number of surveys to report on the adolescent’s pubertal development, mental health, social environment and life events; adolescents also report on various indices of self-perception and social-emotional functioning. Discussion: The knowledge gained from this study will include developmental trajectories of pubertal, neurological, and social processes and their roles as mechanisms in predicting emergence of mental illness in female adolescents. This knowledge will help identify modifiable, developmentally specific risk factors as targets for early intervention and prevention efforts. 1Although the study was advertised using the name Transitions in Adolescent Girls, during the first wave of data collection 1.7% of participants reported a non-binary gender identity. Thus while title and abstract refer to ‘girls’ and ‘female’, we realize that not all participants identify as such. See methods for details.